Characterisation of REBCO Roebel cables - Otten, Simon J. (Karlsruher Schriftenreihe zur Supraleitung / Hrsg. Prof. Dr.-Ing. M. Noe, Prof. Dr. rer. nat. M. Siegel, 2019)
This work concerns the characterization of high-temperature superconducting REBCO Roebel cables for use in accelerator magnets. The effects of bending, torsion and compressive stress on the cable are investigated. The second part concerns the effect of inter-strand resistance on the cable properties. A two-parameter model is proposed to describe inter-strand connections and predict the effect on AC loss and stability. Additionally, the AC loss and stability are experimentally investigated.